Self-regulation of learning in university students: a descriptive study - Burbano-Larrea, Pablo (2021)
Among the fundamental capacities that the human being must have to achieve successful development at a personal, academic and professional level is the self-regulation of learning. Managing resources and strategies in knowledge construction processes is essential. Only in this way can goal-oriented performance and training results be planned, executed, monitored and evaluated. Within this order of ideas, the objective of this work was to determine the self-regulation of learning in students of the Faculty of Philosophy, Letters and Education Sciences, of the Central University of Ecuador. It was developed from a quantitative approach and a descriptive level, being a cross-sectional study. The discoveries found allowed us to conclude that those research group mostly present low and medium-low levels of self-regulation, with similar results in the analysis by sex and by level of training. Likewise, it was possible to identify that the levels: low and medium low are prevalent among students in the various factors of this variable. Being these: planning, cognition management, motivation management, understanding assessment and context management. When contrasting these results with other studies, coincidences and contradictions were observed. This indicates the need to deepen the investigation of this variable. It is suggested to generate curricular innovations in university education that allow the development of self-regulation of learning throughout their professional training.